QUALITY NORMS DEVELOPMENT, STUDY OF STABILITY AND ESTABLISHMENT OF SHELF-LIFE OF COSMECEUTICAL FORMS OF SCHIZANDRA CHINENSIS - M. S. Makieva; Yu. A. Morozov (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
There are results of experimental studies in the quality norms, stability study and establishment of shelf-life of cosmeceutical forms with CO2 extract of Schizandra chinensis seeds using UV spectr ophotometryand chromatographic analysis methods. The quality norms established may be recommended for normative documentation stipulation in future. The approximate shelf-life for the napkins under study was 24 months.